The experience of consciousness-raising in abused women - Donna M. Chovanec (Adult Education Research Conference, 1993)
This study suggests a process by which battered women experience emancipatory learning. The participants identify three themes common to a definition of consciousness-raising, i.e., a sense of personal power, realization of societal power, and action. This qualitative research process draws upon feminist research, participatory research and grounded theory method.